Understanding Quality Paradigm Shifts in the Evolving Pharmaceutical Landscape: Perspectives from the USP Quality Advisory Group - Jane Weitzel; Horacio Pappa; Gregory M. Banik; Amy R. Barker; Elizabeth Bladen; Narendra Chirmule; Joseph DeFeo; Jennifer Devine; Steven Emrick; Taha Kass Hout; Michael S. Levy; Gugu N. Mahlangu; et al. (The AAPS Journal, 2021)
Recent changes in the pharmaceutical industry have led to significant paradigm shifts in the pharmaceutical quality environment. Globalization of the pharmaceutical industry, increasingly rapid development of novel therapies, and adoption of new manufacturing techniques have presented numerous challenges for the established regulatory framework and quality environment and are impacting the approaches utilized to ensure the quality of pharmaceutical products. Regulators, industry, and standards-setting organizations have begun to recognize the need to rely more on integrated risk-based approaches and to create more nimble and flexible standards to complement these efforts. They also increasingly have recognized that quality needs to be built into systems and processes throughout the lifecycle of the product. Moreover, the recent COVID-19 crisis has emphasized the need to adopt practices that better promote global supply chain resilience. In this paper, the USP Quality Advisory Group explores the various paradigm shifts currently impacting pharmaceutical quality and the approaches that are being taken to adapt to this new environment. Broad adoption of the Analytical Procedure Lifecycle approach, improved data management, and utilization of digital technologies are identified as potential solutions that can help meet the challenges of these quality paradigm shifts. Further discussion and collaboration among stakeholders are needed to pursue these and other solutions that can ensure a continued focus on quality while facilitating pharmaceutical innovation and development.